COVID-19 Impact on Rural Men and Women in Nigeria, Round 4 - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
This dataset is the result of a phone survey set up to measure the impact of COVID-19 on rural people in Nigeria. As most governments have urged the population to stay at home to slow down the transmission of the disease, the impact of COVID-19 can affect women and men in different ways: as an income shock (directly or indirectly); as a health and caring shock; as a shock of mobility (affecting access to water, food, firewood, schooling); and as a risk of increased domestic conflict and violence. To capture these various effects on household welfare, this phone survey was conducted with (around) 500 individuals randomly drawn from an existing list of phone numbers collected from previous household surveys with an equal proportion of women and men. The same individuals were also interviewed during other rounds to generate a longitudinal panel allowing to analyze the impact of COVID-19 through time.